New energy levels, calculated lifetimes and transition probabilities in Xe IX - Gallardo, Mario Oscar (2011)
Twenty-one new experimental energy levels belonging to the 4d96p, 4d94f and 4d95f configurations of Xe IX are presented. They have been deduced from 75 newly classified lines involving the configurations 4d95p, 4d96p, 4d94f, 4d95f and 4d95d, 4d95s, 4d96s for the odd and even parities, respectively. The radiative lifetimes of these levels as well as the weighted oscillator strengths and transition probabilities for all the observed spectral lines have been calculated with optimized parameters deduced from a least-squares fitting procedure applied in the framework of a relativistic Hartree–Fock method including core-polarization effects. The scale of transition probabilities has also been assessed through comparisons with lifetimes calculated using a relativistic multiconfigurational Dirac–Fock approach.